A novel missense variant in IDH3A causes autosomal recessive retinitis pigmentosa. (4th March 2019) - Peter, Virginie G.; Nikopoulos, Konstantinos; Quinodoz, Mathieu; Granse, Lotta; Farinelli, Pietro; Superti-Furga, Andrea; Andréasson, Sten; Rivolta, Carlo
ABSTRACT: Background: Inherited retinal degenerations (IRDs) encompass a wide spectrum of genetic ocular diseases characterized by considerable genetic and clinical heterogeneity. Methods: Complete ophthalmic examination and next-generation sequencing. Results: We describe a patient with no family history of vision loss, who at the age of 28 years developed visual impairment consistent with a severe form of retinitis pigmentosa. Genetic testing by means of whole exome sequencing identified a homozygous variant in the gene IDH3A . To date, only three papers have reported mutations in IDH3A, in families with early-onset retinal degeneration with or without the presence of macular pseudocoloboma. Conclusion: This study highlights the importance of including this rarely-mutated gene in the molecular diagnostic set-ups for IRDs, and further delineates the phenotypic spectrum elicited by mutations in IDH3A .